Damping capacity of shape memory alloys - Ng, Chun Yong (2014)
High damping materials have been attracting much interest and attention in engineering applications. However, little research has been done on the heat-dependent effects on damping capacity of a material if subjected to heating or isothermal environment. Shape Memory Alloys (SMAs) such as NiTi have shown that it can exhibit high damping capacity, excellent shape memory effect and superelasticity. It is known that the damping capacity of a material varies under different external parameters (i.e. frequency and stress). The main purpose of this study is to investigate how the damping capacity would be affected by different external parameter and also the influence of heat effects on damping when material is working under an environment with and without temperature variation.